Obtenção de cerâmicas de alumina via fotopolimerização em cuba: efeitos da concentração de sólidos, do empacotamento de partículas e de aditivos de sinterização - Verza, Jhonata Rafael (Universidade Federal de São Carlos, 2025)
Vat photopolymerization-based additive manufacturing is a promising technique for the fabrication of ceramic components with complex geometries, high dimensional accuracy, and excellent surface finish. However, its application to the production of technical ceramics still faces challenges such as the formulation of photocurable suspensions with high solid content and low viscosity, interlayer adhesion during printing, and the efficient removal of the organic phase without inducing structural defects. When not properly addressed, these limitations compromise part integrity, promoting the formation of cracks, delaminations, and loss of mechanical performance. This research proposed an approach to producing alumina-based ceramic parts using vat photopolymerization 3D printing, with a focus on achieving dense microstructures. To this end, the following strategies were employed: (i) careful selection of raw materials; (ii) application of the Alfred particle packing model to optimize the suspensions; and (iii) incorporation of sintering additives (Nb2O5, TiO2 , and MnO2) to promote liquid-phase sintering and enhance final densification. The results showed that the suspension containing 50 vol.% of Al2O3 exhibited stable rheological behavior and suitable viscosity for DLP processing. After sintering at 1600 °C, the printed parts achieved a relative density of 90.1 % and a flexural strength of 74.5 MPa. The optimization of the suspension formulation using the Alfred model led to a viscosity reduction of up to 77 %, improving printability. However, variations in cure depth during printing resulted in delaminations and cracks after thermal treatment. Additionally, the incorporation of sintering additives such as MnO2 and TiO2 into the photocurable suspensions significantly improved the densification of the resulting ceramics, achieving relative densities of up to 95.2 % and a maximum flexural strength of 80.9 MPa. Therefore, this study demonstrates the feasibility of producing dense ceramics via vat photopolymerization by combining careful raw material selection with optimized formulation and liquid-phase sintering strategies.
Obtaining alumina ceramics via vat photopolymerization: effects of solid content, particle packing, and sintering additives
Keywords: Manufatura aditiva; Suspensão; Sinterização; Fotopolimerização; Alumina; Additive manufacturing; Suspension; Sintering; Photopolymerization; Alumina; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA